Experimental and Confining Pressure Analysis of Steel Clamp Confined Unreinforced Concrete Subjected to Axial Concentric Load - Yansiku, Sandy I.; Chandra, Jimmy (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2025)
Vertical cracks and spalling of the concrete cover in reinforced concrete structures are examples of failure modes of concrete columns due to repeated earthquake loads. Strengthening methods have been introduced including external jacketing using costly carbon FRP. This study investigated external strengthening of cylindrical concrete using low-cost thin steel confining sheets subjected to concentric axial loads. The experimental works in this study tested the tensile strength of the confining steel elements, the compressive strength of unconfined and confined cylindrical concrete. The composition of the steel confining elements is positioned in such that it could generate an optimal confinement effect and prevent local buckling. This study also developed the formulation of the confining stress and ultimate axial load based on the test results of the current study and past research data. The results showed that the use of steel clamp elements improves the axial strength and axial deformation of cylindrical concrete columns by over 200% without buckling of the clamp elements. The external confinement method can reduce vertical cracks and strain localization that usually occur in conventional cylindrical concrete. The proposed formulation of the confining stress and the ultimate axial load provided accurate results compared to the experimental results.